Karamah perspektif tasawuf dan realitas sosial: Studi kritis terhadap pemahaman masyarakat kontemporer - adikumoro, anugrah candra (Maliki Interdisciplinary Journal, 2026)
Karamah is one of the central concepts in the Islamic Sufi tradition, referring to the extraordinary gifts or abilities bestowed by Allah upon His saints (awliya’). This study aims to critically analyze contemporary society’s understanding of the concept of karamah from a Sufi perspective, as well as examine its relevance in today’s social reality. This research employs a qualitative-descriptive approach through library research, analyzing classical Sufi sources and relevant contemporary literature. The findings reveal that karamah in classical Sufi perspective is understood as a sign of a saint’s perseverance in drawing closer to Allah, not as a tool for seeking public attention or popularity. However, in the social reality of contemporary society, the understanding of karamah often experiences distortion, where it is frequently associated with supernatural attractions for entertainment, or even exploited for particular interests. This study concludes that a deeper and more scholarly understanding of the concept of karamah is necessary so that society does not fall into misconceptions that deviate from the true substance of Sufi teachings.